2007
DOI: 10.1111/j.1651-2227.2007.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of adiposity measures with blood lipids and blood pressure in children aged 8–11 years

Abstract: %BF from BIA is more strongly associated than either BMI or TST with most of the blood lipid fractions in schoolchildren aged 8-11 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…In these papers, we found that general risk parameters for cardiovascular disease were worsened by high body mass index. Body mass index was positively associated with systolic blood pressure in five studies,40 42 43 44 45 diastolic blood pressure in four studies,42 43 44 45 total cholesterol in one study,46 LDL cholesterol in three studies,43 45 46 triglycerides in three studies,43 45 46 and left ventricular mass in one study,47 and inversely associated with HDL cholesterol in two studies 4546 Body mass index was also associated with cardiovascular disease risk parameter clustering,43 44 48 49 50 51 and one study found the metabolic syndrome to be present in a statistically significant number of its overweight sample 48…”
Section: Resultsmentioning
confidence: 99%
“…In these papers, we found that general risk parameters for cardiovascular disease were worsened by high body mass index. Body mass index was positively associated with systolic blood pressure in five studies,40 42 43 44 45 diastolic blood pressure in four studies,42 43 44 45 total cholesterol in one study,46 LDL cholesterol in three studies,43 45 46 triglycerides in three studies,43 45 46 and left ventricular mass in one study,47 and inversely associated with HDL cholesterol in two studies 4546 Body mass index was also associated with cardiovascular disease risk parameter clustering,43 44 48 49 50 51 and one study found the metabolic syndrome to be present in a statistically significant number of its overweight sample 48…”
Section: Resultsmentioning
confidence: 99%
“…While the healthiest body fat percentages associated with the lowest mortality and mobidity have not been established, ranges of 12% to 20% for men and 20% to 30% for women have been suggested (Abernathy and Black 1996). Normal weight obesity has been linked with dyslipidemia, hypertension, hyperglycemia, heart disease, and all-cause and cardiovascular mortality (Daniels et al 1999;Dervaux et al 2008;Gómez-Ambrosi et al 2011;Musso et al 2011;Ridker et al 2003;Romero-Corral et al 2010;Vizcaíno et al 2007). While initially no participants had BMIs in the normal range coupled with "excessive" percent body fat, by the end of the study, 1 male and 3 females (3% of the study group) had BMIs in the normal range but ≥20% and 30% body fat, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Both obesity (defined as a body mass index (BMI) ≥ 30 kg•m -2 ) and "normal weight obesity" (i.e., having a BMI in the normal range of 18.5 to 24.9 kg•m -2 but having excessive body fat) are associated with a multitude of health prob-lems. While obesity has been linked with an increased risk of hyperlipidemia, heart disease, hypertension, and stroke, among others, normal weight obesity or greater adiposity has been linked with dyslipidemia, hypertension, and hyperglycemia (Daniels et al 1999;Dervaux et al 2008;Gómez-Ambrosi et al 2011;Romero-Corral et al 2010;Vizcaíno et al 2007) as well as with elevated plasma C-reactive protein concentrations, an indicator of inflammation (Musso et al 2011;Ridker et al 2003). Moreover, recent studies, which have included adults aged as young as 20 years, have found that gains in body fat are positively associated with heart disease as well as all-cause mortality and cardiovascular mortality (Romero-Corral et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies propose other adiposity measures like waist circumference (Maffeis et al, 2001) or percentage body fat by bioimpedance (Martínez Vizcaíno et al, 2007), BMI continues to be an appropriate measure for estimating cardiovascular risk in children and adolescents (Plachta‐Danielzik et al, 2008).…”
Section: Discussionmentioning
confidence: 99%